Іронія як чинник жанрових модуляцій у п'єсі Івана Тобілевича (Карпенка-Карого) "Розумний і дурень" - Оладько, Т. (Літературознавчі обрії. Праці молодих учених, 2010)
The article deals with the transformation of genre of the play «Rozumny i duren’», which the author called a «comedy». Analyzing the play we show that melodrama is actually the essential principle of its structure and I. Tobilevych tries to overcome it and sneers at this principle. Thus irony in the play becomes a factor of modulation of melodramatic genre into ironical comedy, revealing generic ambiguity of the play «Rozumny i duren’».